IMPROVING LESSON PLANS AND TEAMWORK THROUGH PEER COLLABORATION AT WAHIDIYAH UNIVERSITY - Kusnawawati, Edi Titik; Wachid, Nur; Kamam, Badrul; Setyawan, Wawan Herry (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2026)
This classroom action research aimed to enhance the pedagogical competence of pre-service English teachers by implementing a Peer-Collaborative Lesson Design (PCLD) strategy in the Learning and Teaching course. The study sought to: (1) analyze the improvement in the quality of Lesson Plans (RPP) developed by students, and (2) investigate the development of students' collaborative skills. Conducted over two cycles at FKIP Universitas Wahidiyah with 30 participants, the study employed a convergent parallel mixed-methods design. Quantitative data were derived from pre-test and post-test RPP scores assessed via a validated analytic rubric, while qualitative data were collected through participatory observation, student reflection journals, and focus group discussions. Findings revealed a statistically significant increase in RPP quality, accompanied by notable improvements in learning activity design and assessment alignment. Qualitative analysis revealed a significant shift in collaborative dynamics, from initial task division to sophisticated co-creation and constructive peer feedback. The study concludes that the structured PCLD strategy effectively bridges the theory-practice gap in lesson planning pedagogy and fosters essential collaborative competencies, offering a replicable model for similar educational contexts.